2010
DOI: 10.1136/gut.2010.223586
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of confocal laser endomicroscopy for gastric superficial cancerous lesions

Abstract: CLE can be used to identify gastric superficial cancer/HGIN lesions with high validity and reliability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
100
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(106 citation statements)
references
References 27 publications
(29 reference statements)
4
100
0
2
Order By: Relevance
“…Yao [33] reported that finding a white opaque substance on magnified endoscope with narrow band imaging differentiates intraepithelial neoplasia with a sensitivity of 94% and a specificity of 96%. Moreover, confocal laser endomicroscopy is reported to identify gastric superficial cancer/HGIN lesions with high validity and reliability compared to conventional white-light endoscopy and histological analysis for the final diagnosis [34] . Although image-enhanced endoscopy and confocal laser endomicroscopy are promising methods and modalities to improve the pre-therapeutic diagnostic accuracy of intraepithelial neoplasia, it is not yet clear whether they are clinically useful because of expert bias.…”
mentioning
confidence: 99%
“…Yao [33] reported that finding a white opaque substance on magnified endoscope with narrow band imaging differentiates intraepithelial neoplasia with a sensitivity of 94% and a specificity of 96%. Moreover, confocal laser endomicroscopy is reported to identify gastric superficial cancer/HGIN lesions with high validity and reliability compared to conventional white-light endoscopy and histological analysis for the final diagnosis [34] . Although image-enhanced endoscopy and confocal laser endomicroscopy are promising methods and modalities to improve the pre-therapeutic diagnostic accuracy of intraepithelial neoplasia, it is not yet clear whether they are clinically useful because of expert bias.…”
mentioning
confidence: 99%
“…27,28,[31][32][33] Recent studies further evaluated the benefit of conventional CLE to both diagnose and guide endoscopic resection of gastric neoplasia by visualizing histomorphological alterations. 28,34,35 In contrast, we aimed at establishing protocols for molecular staining with both diagnostic and therapeutic anti- bodies in our xenograft model. This could translate into 2 different clinical situations: first, the early detection of gastric cancer in screening patients and, second, the molecular characterization of a given lesion in a (suspected) cancer patient.…”
Section: Discussionmentioning
confidence: 97%
“…11,12 However, confocal laser endomicroscopy has the limitation of imaging at a depth of approximately 250 μm from the mucosal surface and the increased phototoxicity for gastrointestinal mucosa. Thus, the development of a multiphoton (or two-photon) endomicroscopy could, therefore, provide deeper penetration imaging and less phototoxicity, allowing a high-resolution in vivo real-time histopathology of gastrointestinal diseases in clinical practice.…”
Section: Discussionmentioning
confidence: 99%